The Role of Angiotensin Converting Enzyme 1 Insertion/Deletion Genetic Polymorphism in the Risk and Severity of COVID-19 Infection - Saad, Halim; Jabotian, Karna; Sakr, Carine; Mahfouz, Rami; Akl, Imad Bou; Zgheib, Nathalie K. (Frontiers in Medicine, 2021)
Background: Individuals infected with the COVID-19 virus present with different symptoms of varying severity. In addition, not all individuals are infected despite exposure. Risk factors such as age, sex, and comorbidities play a major role in this variability; however, genetics may also be important in driving the differences in the incidence and prognosis of the disease. An Insertion/Deletion (I/D) polymorphism in the ACE1 gene (rs1799752) may explain these genetic differences. The aims of this study were to determine the potential role of ACE1 I/D genetic polymorphism in the risk of contracting COVID-19 as well as predicting the severity of COVID-19 infection. Methods: Three-hundred and eighty-seven non-related Lebanese subjects, 155 controls and 232 cases, who presented to the American University of Beirut Medical Center (AUBMC) for COVID-19 PCR testing were recruited. Clinical data were collected via filling a questionnaire and accessing the medical records. Peripheral blood was withdrawn for DNA isolation, and genotyping performed with standard PCR followed by band visualization on agarose gel. Results: In our study population, previously described risk factors such as gender, age, and comorbidities were associated with increase in disease susceptibility and severity. ACE1 I was the least common allele, and there was a positive association between ACE1 I and the risk of contracting the COVID-19 disease. More specifically, the frequency of II genotype was significantly higher among cases when compared to controls (P = 0.035) with individuals with the II genotype having greater risk for contracting the COVID-19 disease: OR = 2.074, P = 0.048 in the multivariate analysis. As for disease severity, the DD genotype and D allele were associated with increased risk for developing severe symptoms (OR = 2.845, P = 0.026 and OR = 2.359, P = 0.014, respectively), and the DD genotype with necessitating hospitalization (OR = 2.307, P = 0.042). In parallel, D allele carriers showed a significantly increased risk for developing hypoxia: OR = 4.374, P = 0.045. Conclusion: We found a positive association between ACE1 I and the risk of contracting the COVID-19 disease, and between ACE1 D and a worse outcome of the COVID-19 infection. Therefore, genotyping for ACE1 I/D polymorphism could be used to assess risk and predict severity for better prognosis and management of the disease.